Design modifications of dynamically loaded structures using structural optimization / Aizzat Sazali Yahaya Rashid - Aizzat Sazali, Yahaya Rashid (2014)
The main aim of this study is to introduce modifications or reinforcements to the design of dynamically loaded structures by using structural optimization method. Two conditions of structural dynamic modification using structural optimization were examined, namely SDM for existing structure, and SDM at conceptual stage. The study aims at assessing the efficacy of structural optimization approach in ascertaining optimum solutions in SDM compared to the conventional approach employing Finite Element Analysis (FEA). Modal analysis was employed to find the natural frequencies and the corresponding mode shapes experimentally using Experimental Modal Analysis (EMA) and Operating Deflection Shape (ODS) while computationally using Finite Element Method (FEM). For the existing structure, it is found that the frequency of the first mode of the test rig is lower than the normal operating frequency which is about 20 Hz, so improvements were made to maximize the first mode. The process resulted in shifting the frequency to about 16-18 Hz which is still below the recommended value. For the structure in conceptual stage, the first torsion and first bending mode of a Body-in-white (BIW) of a compact 5-door hatchback were set to be above 40 and 60 Hz, respectively, using structural optimization. The process was successful in satisfying the objective of increasing the frequencies but with certain drawbacks such as added mass. In addition, different methods of optimization were also utilized such as changing the order of approach or performing two types of optimization simultaneously to demonstrate better results. Conclusively, structural optimization was a viable method of improving the dynamic characteristics of structures without trial and error process or previous experience.